2014
DOI: 10.1007/s00223-014-9908-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Atypical Femoral Fractures—A Retrospective Review

Abstract: Subtrochanteric atypical femoral fractures (AFFs) have been reported in patients on osteoporosis therapy (bisphosphonates and denosumab). In 2010, and again in 2013, the ASBMR AFF Task Force developed strict diagnostic criteria for AFFs. This is the first study using these criteria to define the prevalence of AFFs in Canada. This study is a retrospective review of all adult patients (April 2002-March 2013) with an ICD 10 code for hip, femoral or subtrochanteric fracture, from two referral hospitals in Alberta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The major differences between the original and revised definitions are as follows: (1) periosteal or endosteal thickening of lateral cortex at the fracture site (“beaking or flaring”) was changed from a minor to a major feature, (2) minimal comminution was permitted, and (3) the wording “transverse or short oblique configuration” was expanded to specify that the fracture line must originate at the lateral cortex and remain transverse across the cortex, but permitted the fracture line to become oblique as it progressed medially across the femur. Recent studies, using the 2013 case definition and a variety of designs, report a low incidence of AFFs [ 6 , 7 ••, 8 ••, 9 , 10 ].…”
Section: Atypical Femur Fracture Case Definitionmentioning
confidence: 99%
“…The major differences between the original and revised definitions are as follows: (1) periosteal or endosteal thickening of lateral cortex at the fracture site (“beaking or flaring”) was changed from a minor to a major feature, (2) minimal comminution was permitted, and (3) the wording “transverse or short oblique configuration” was expanded to specify that the fracture line must originate at the lateral cortex and remain transverse across the cortex, but permitted the fracture line to become oblique as it progressed medially across the femur. Recent studies, using the 2013 case definition and a variety of designs, report a low incidence of AFFs [ 6 , 7 ••, 8 ••, 9 , 10 ].…”
Section: Atypical Femur Fracture Case Definitionmentioning
confidence: 99%
“…Using the first ASBMR definition, the prevalence of AFFs accounted for only 0.2-0.8% of total hip fractures and 3.5-30.3% of subtrochanteric and femoral shaft fractures (13,(17)(18)(19)(20). Similarly, three studies using the revised ASBMR definition reported a low prevalence of AFFs, estimated to be 0.63% of total hip fractures and 3.5-5.7% of subtrochanteric and femoral shaft fractures (22,24,25).…”
Section: The Epidemiology Of Affsmentioning
confidence: 99%
“…In all studies except for one, the mean age of patients with AFFs were reported to be above 65 years (Table 1) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Amongst these studies, six retrospective case-control studies showed that patients with bisphosphonate-related AFFs were younger than patients with typical proximal femoral fractures (TPFFs) (mean age range of 66-75 years versus 75-89 years respectively), at the time of fracture (12-15, 19, 22).…”
Section: Epidemiology and Postoperative Outcomes Of Atypical Femoral mentioning
confidence: 99%
“…When BPs are stopped, the risk of AFF declines (8). There have been reports of AFF with denosumab which is another antiresorptive agent (8,9). The pathogenesis of AFF can be related to long-term suppression of bone turnover.…”
Section: Introductionmentioning
confidence: 99%